Validation of the Use of Anthocyanin as Indicators for Acid-Base Titration - Lilis Tuslinah; Laras Rizkia Widyastuti; Mochamad Fathurohman (Jurnal Kimia Sains dan Aplikasi, 2025)
Rambutan peel (Nephelium lappaceum L.) contains secondary metabolites, particularly flavonoids, including anthocyanins. Anthocyanins exhibit color changes in response to variations in pH, making them potential candidates for use as acid-base indicators. This study aims to validate using methanol fraction powder derived from rambutan peel as an acid-base titration indicator by evaluating method validation parameters such as precision, accuracy, and linearity. The fractionation process was conducted using liquid-liquid extraction with n-hexane, water, and methanol as solvents, followed by freeze-drying of the methanol fraction. The methanol fraction powder was analyzed and compared with the conventional phenolphthalein indicator to determine the color transition at the titration endpoint. The results indicated that the methanol fraction exhibited a color change to brown within a pH range of 8–11. Statistical analysis using an independent sample t-test showed no significant difference between the methanol fraction powder and phenolphthalein (significance value > 0.05). Therefore, based on the method validation results, including precision, accuracy, and linearity, the methanol fraction powder of rambutan peel demonstrates potential as a reliable acid-base indicator.